Improving Health Profiles and Type 2 Diabetes Mellitus Knowledge of Community Groups in Karanglo Village, Grogol, Sukoharjo, Central Java, Indonesia Through the SEE Method - Aisyah, Riandini; Mahmudah, Nur; Candrasari, Anika; Sintowati, Retno; Bestari, Rochmadina Suci; Rosyidah, Devi Usdiana; Supraba, Intan Pratiwi; Utami, Indari (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
Central Java ranks fourth among regions for the highest number of diabetes melitus (DM) cases, following Jakarta, Yogyakarta, and East Kalimantan. Grogol District in Sukoharjo Regency had the greatest prevalence of DM cases in 2019, accounting for 18.41% of the total. Diabetes melitus significantly impairs the overall well-being of individuals as it affects individuals across all age groups, including those who can work and those who cannot. If left unmanaged, it can lead to a range of outcomes. The Karanglo Village community is considered at high risk for diabetes melitus (DM) due to a history of health ailments and elevated blood glucose levels. Furthermore, this region is still lacking any health education interventions. This activity aimed to do earlier screening and monitoring of blood sugar levels, as well as providing health education, using the SEE approach (Screening, Health Education, and Exercise) to monitor diabetes melitus. The program was implemented in the period from November 2023 to January 2024, which includes a total of 27 participants, all of whom are female. The implementation of the programs involves the following methods: conducting blood sugar level screenings, engaging in diabetes exercises twice a week, providing health education in six meetings that cover topics such as the epidemiology and etiology, risk factors and prevention, symptoms and diagnosis, complications and management of DM, as well as blood glucose monitoring. Apart from using tools in the form of presentation slides, health education also utilized educational posters. At the end of the program, there was an increase in knowledge by 21.5% (p=0.024) based on pretest and posttest scores, improvements in blood sugar levels, total cholesterol levels, and body mass index. To follow up on the program, a group of independent blood sugar observers has been formed who is responsible for further monitoring blood sugar in program participants.